2022
DOI: 10.3390/molecules27020359
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Chiral Cyclic Compounds Enabled by Enantioselective Photocatalysis

Abstract: Chiral cyclic molecules are some of the most important compounds in nature, and are widely used in the fields of drugs, materials, synthesis, etc. Enantioselective photocatalysis has become a powerful tool for organic synthesis of chiral cyclic molecules. Herein, this review summarized the research progress in the synthesis of chiral cyclic compounds by photocatalytic cycloaddition reaction in the past 5 years, and expounded the reaction conditions, characters, and corresponding proposed mechanism, hoping to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The [2 + 2] photocycloaddition reaction is a typical photochemical reaction for the formation of four-membered rings, which can occur either by direct excitation of substrates or through photocatalysts. One of the most famous photocycloadditions is the Paternò-Büchi reaction, which involves carbonyl derivatives and alkenes to form oxetanes (Scheme a). This reaction is activated by direct excitation of carbonyl derivatives and subsequent CC double bond engagement . Li et al advanced this photocycloaddition by direct excitation of noncovalent complexes comprising alkene and carbonyl substrates under visible-light irradiation, providing fresh insights into the extensively studied Paternò-Büchi reaction (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The [2 + 2] photocycloaddition reaction is a typical photochemical reaction for the formation of four-membered rings, which can occur either by direct excitation of substrates or through photocatalysts. One of the most famous photocycloadditions is the Paternò-Büchi reaction, which involves carbonyl derivatives and alkenes to form oxetanes (Scheme a). This reaction is activated by direct excitation of carbonyl derivatives and subsequent CC double bond engagement . Li et al advanced this photocycloaddition by direct excitation of noncovalent complexes comprising alkene and carbonyl substrates under visible-light irradiation, providing fresh insights into the extensively studied Paternò-Büchi reaction (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%
“…However, these photocycloaddition reactions without photocatalysts are generally limited by the direct excitation of specific substrates. For the general synthesis of oxetanes via the Paternò-Büchi reaction, a good option is using photocatalysts, among which organometallic complexes are excellent candidates because of their strong light absorption, excellent chemical stability, and long triplet-state lifetime. ,,,, Becker et al reported a visible-light-driven intramolecular aza Paternò-Büchi reaction to produce azetidines from imines and alkenes using an Ir photocatalyst (Scheme c) . The selective activation of the alkene moiety is triggered by energy transfer from the Ir complex.…”
Section: Introductionmentioning
confidence: 99%